Winfred Overholser papers - Overholser, Winfred, 1892-1964.
Correspondence, speeches, writings, scrapbooks, printed matter, photographs, and other papers relating to Overholser's career in psychiatry and his research in forensic psychiatry. Documents his work as commissioner of the Massachusetts Department of Mental Diseases, director of the department's Division for the Examination of Prisoners, and superintendent of Saint Elizabeth's Hospital, Washington, D.C. Correspondents include Harold H. Burton, C.G. Jung, Evalyn Walsh McLean, Karl A. Menninger, Richard M. Nixon, Ezra Pound, Nelson A. Rockefeller, Franklin D. Roosevelt, George Santayana, and Gregory Zilboorg.
Psychiatrist, educator, and superintendent of St. Elizabeth's Hospital, Washington, D.C.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Burton, Harold H. -- 1888-1964 -- Correspondence; Jung, C. G. -- 1875-1961 -- Correspondence; McLean, Evalyn Walsh, -- 1886-1947 -- Correspondence; Menninger, Karl A. -- 1893-1990 -- Correspondence; Nixon, Richard M. -- 1913-1994 -- Correspondence; Pound, Ezra, -- 1885-1972 -- Correspondence; Rockefeller, Nelson A. -- 1908-1979 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Santayana, George, -- 1863-1952 -- Correspondence; Zilboorg, Gregory, -- 1890-1959.; Massachusetts. -- Department of Mental Diseases; Massachusetts. -- Department of Mental Diseases. -- Division for the Examination of Prisoners; Saint Elizabeth's Hospital (Washington, D.C.); Forensic psychiatry; Mental health -- Massachussetts; Prisoners -- Mental health services -- Massachusetts; Psychiatric hospitals -- Washington (D.C.); Psychiatry; Administrators; Educators; Psychiatrists